Air Conditioning Performance Assessment in an Educational Building: A Case Study in Malaysia’s Hot and Humid Region - M.M.S. Dezfouli; A.R. Dehghani-Sanij; Sh. Rostami; R. Suhairi; K. Kadir (International Journal of Integrated Engineering, 2024)
In regions with high temperatures and humidities, the operation of air conditioning (AC) systems accounts for a sizable portion of buildings’ energy use, ranging from 60% to 70%. This energy expenditure is necessary to maintain a thermally comfortable environment inside interior spaces. Therefore, the inadequate functioning of the cooling system has a significant impact on both energy usage and the interior thermal comfort conditions inside the building. Excessive cooling is a common phenomenon observed in Malaysian buildings, with educational institutions and libraries being especially affected. This research aims to identify the underlying cause of excessive cooling in an educational building by assessing the thermal comfort and energy consumption of a fan coil unit (FCU) placed in a selected room in Malaysia’s hot and humid environment. A data acquisition system, comprising sensors and a data logger, was set up in multiple locations inside the case study room and the cooling system. This system was used to quantify performance variables, namely temperature, humidity, and airflow, across four FCU process air lines. The measurement data were gathered from 8 a.m. to 6 p.m. over the course of one week. The collected data was utilized for the purpose of conducting data analysis in order to determine the distribution of cooling load, evaluate thermal comfort, and calculate the energy consumption of the FCU. The findings of the cooling load analysis indicate that 52% of the total cooling load, amounting to 9.4 kW, may be attributed to latent loads, while the remaining 48% is associated with sensible loads. The findings of the thermal comfort investigation reveal that the temperature and relative humidity inside the classroom during the operation of the FCU were recorded as 24.3 °C and 77.1%, respectively. These values do not align with the desired thermal comfort level of 25 °C and 50% humidity. It was discovered that due to the high latent load of the classroom, the FCU is unable to control the humidity level to the appropriate value; therefore, in order to control the humidity, the sensible cooling will be drastically reduced, and overcooling will occur in the space. To attain the optimal interior atmosphere, an optimized FCU has been designed. Compared to the current FCU, the optimized FCU consumes 1.4 times more energy.